Understanding Co-Production as a Policy Tool: Integrating New Public Governance and Comparative Policy Theory - Michael Howlett (2018)
© 2017 The Editor, Journal of Comparative Policy Analysis: Research and Practice. Co-production is an area of policy making in many countries which has received little treatment in the policy studies literature. It has been studied in the field of public administration and public management however, albeit mainly in the case of education-related activities in Scandinavian countries. Using the cases of co-production of support services for the disabled and the elderly in the little-studied programs found in Croatia and Thailand as illustrative examples, this article examines how the concept of co-production can be viewed as an example of the use of a new policy tool, bringing together the insights of both policy and management theory in order to understand its origins and evolution. The article highlights the importance of viewing co-production using an integrated lens if studies of co-production are to advance.